VD_FINDINFO HC / 2011 / 372 vom 19. April 2011 - VD Tribunal cantonal (2011)
ASSURANCE RC AUTO, APPRÉCIATION DES PREUVES, INTERDICTION DE L'ARBITRAIRE | 4 al. 2 CPC, 444 al. 1 ch. 3 CPC, 444 al. 2 CPC